Structural Shifts and Information Density of Complex Noun Phrases in Sinta 2 Abstract: A Translation Study - Syahmiarni Syahmiarni; Veni Roza; Widya Syafitri (Universitas Galuh, 2026)
This study examines structural shifts and information density in the translation of Complex Noun Phrases (CNPs) from Indonesian into English in Sinta 2-accredited bilingual journal abstracts. Grounded in Catford's (1965) framework of structural shift and Halliday's (1985) lexical density formula as a measurement instrument for information density, the study addresses three research questions: (1) how CNPs are structurally restructured in Indonesian-English translation; (2) what linguistic mechanisms characterize those structural shifts; and (3) how structural shifts relate to information density in translated CNPs. A descriptive qualitative design was employed, with data consisting of 110 CNPs extracted from fifteen purposively selected bilingual abstracts across five Sinta 2 ELT and linguistics journals published between 2021 and 2026. Findings reveal that structural shifts occurred consistently across all fifteen abstracts, with four predominant mechanisms: modifier-head reordering (43.6%), modification pattern change (26.4%), constituent expansion or reduction (17.3%), and grammatical relation transformation (12.7%). Information density effects were variable: some shifts increased density by compressing meaning into compact English premodifier stacks, others preserved informational equivalence, and a smaller number reduced density when nominalized source-language concepts were merged into more general target-language expressions. These findings reveal a tension in academic translation between grammatical naturalness and conceptual precision, contributing to translation studies by integrating structural and functional perspectives on Indonesian-English academic translation.